The Effect of Administration of Lactobacillus Probiotics on Secretoric Immunoglobulin A (s-IgA) Levels in Female Wistar Post Ovariectomy - Safitri, Rani; Aksohini Wijayanti, Tut Rayani (Universitas Syiah Kuala, 2025)
Ovariectomy is a commonly performed medical procedure to investigate the effects of estrogen loss on the immune system. Secretory immunoglobulin A (s-IgA) is an antibody that is important in mucosal defense system. Probiotics, such as Lactobacillus, have been known to affect the local immune system. This study aims to evaluate the effect of administering Lactobacillus probiotics on s-IgA levels in Wistar rats undergoing ovariectomy. Female Wistar rats (n=30) were randomly divided into two groups, namely the treatment group (receiving Lactobacillus probiotics) and the control group (receiving placebo). After undergoing an ovariectomy, treatment was given for 4 weeks. After the treatment period, s-IgA levels were evaluated using the ELISA technique in mouse saliva samples. The results showed that the treatment group receiving Lactobacillus probiotics had significantly higher s-IgA levels than the control group (p 0.05). Administration of Lactobacillus probiotics can increase s-IgA levels in Wistar rats undergoing ovariectomy. This shows the potential of probiotics in enhancing mucosal immune responses in conditions associated with estrogen deficiency